2014
DOI: 10.1007/s00436-014-3905-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and molecular diversity of Acanthamoeba species isolated from public baths in Hungary

Abstract: Hungary has a large number of thermal baths and spa facilities which attract hundreds of thousands of tourists annually. Until recently, however, the free-living amoebae were not of public health concern. Genotyping of Acanthamoeba species, potential agents of keratitis and granulomatous encephalitis, was carried out in 20 Hungarian public baths for the first time to assess the incidence and molecular diversity of the genus in the country. Our results show that 6.7% of the samples were positive for Acanthamoeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Investigations on the distribution of the virulent amoebic strains in different soil, air, and water environments have been conducted worldwide, also with the aid of molecular techniques. Potentially pathogenic strains are detected in environmental samples and reported worldwide [ 18 , 25 , 35 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations on the distribution of the virulent amoebic strains in different soil, air, and water environments have been conducted worldwide, also with the aid of molecular techniques. Potentially pathogenic strains are detected in environmental samples and reported worldwide [ 18 , 25 , 35 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 59.1% of 22 cultured surface and stagnant water samples in Tehran ( 29 ), 35% of 120 water samples (wells and water pipes) in Shiraz ( 30 ), 61.11% of 54 water samples (wells, springs, qanats, and motor houses) in Arak ( 31 ), 30% of 50 environmental water sources (sea, pools, ponds, fountains, and running waters) in various regions of Guilan province ( 32 ), 88% of 93 water specimens from pools and ponds in Sistan & Baluchistan ( 33 ), and 34.44% of 90 pond water samples in Mashhad contaminated with the amoeba ( 34 ). Furthermore, contamination of water sources with FLA has been documented in reports from Egypt (43.2%), Italy (28.7%) ( 35 , 36 ), Thailand (15.9%), China (14.68%), Japan (68.7%), Turkey (22%), and Hungary (41%) ( 37 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with previous studies that detected 51 % and 34 % prevalence in household tap water, all higher than the prevalence in environmental water [ 20 , 21 ]. Previous studies have also indicated that the prevalence of Acanthamoeba in environmental and domestic water can vary from as low as 1 % to as high as 79 % [ 12 , 19 , 22 25 ], all depending on sample size and site.…”
Section: Discussionmentioning
confidence: 99%